THE DETECTIVE FORMULA IN AGATHA CHRISTIE ‘S SLEEPING MURDER: MISS MARPLE IN THE LAST CASE - Priska Kristisakti Lontaan; Agustine Mamentu; Delli Sabudu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study is mainly aimed to reveal the detective formula in Agatha Christie’s Sleeping Murder Miss Marple in the Last Case. In conducting this research, qualitative research is applied since the data is in form of words rather than numbers. In analyzing the operative formula in Agatha Christie’s Sleeping Murder Miss Marple in the Last Case the writer used the structuralism theory. The result of the research shows that there is a detective formula, in the detective story the formula of a detective story is required to arrange the structure and explain how the situation, the pattern of action in this story. In order to solve the crime this happened in Sleeping Murder: Miss Marple in the Last Case. The detective formula centers upon the detective’s investigation and solution of the crime. Exemplify six main phases of this pattern (a) Introduction of the Detective; (b) Crime and Clue; (c) Investigation;  (d) Announcement and the Solution; (e) Explanation of the  Solution; (f) Denouement, all the phases revealed in the novel.